Implementasi Triple Bottom Line dan Pengaruhnya Terhadap Pendapatan Usaha di Kecamatan Jambi Timur Kota Jambi - Windy Sim; Heriberta; Ridwansyah (PT. Hasba Edukasi Mandiri, 2026)
Culinary businesses such as ayam geprek continue to grow rapidly and contribute to local economic activity. The Triple Bottom Line (TBL) framework is one approach that can support business sustainability. This study aims to describe the implementation of the TBL concept and examine its influence on the income of ayam geprek businesses in East Jambi District, Jambi City. The research uses a quantitative approach with descriptive analysis. A saturated sampling method was applied, involving 28 business owners as respondents. Primary data were collected through questionnaires and processed using Microsoft Excel and SPSS. The results show that the economic, social, and environmental aspects of TBL have been applied well, as indicated by the high average scores across indicators. The regression analysis reveals that the economic and social aspects have a positive and significant effect on business income, while the environmental aspect shows a negative and significant effect on the income of ayam geprek businesses in East Jambi District.